2002
DOI: 10.1177/0022002702046001004
|View full text |Cite
|
Sign up to set email alerts
|

Third-party Interventions and the Duration of Intrastate Conflicts

Abstract: Recent research has begun to focus on the role of outside interventions in the duration of civil conflicts. Assuming that interventions are a form of conflict management, ex ante expectations would be that they would reduce a conflict's expected duration. Hypotheses relating the type and timing of outside interventions to the duration of civil conflicts are tested. The data incorporate 150 conflicts during the period from 1945 to 1999, 101 of which had outside interventions. Using a hazard analysis, the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
503
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(520 citation statements)
references
References 20 publications
12
503
0
5
Order By: Relevance
“…In this article, we seek to advance our knowledge of the relationship between civil and international conflict by examining the factors that influence why certain rebel groups receive external support while others do not+ Empirical analyses of external intervention in civil war often examine what type of conflicts are likely to involve external intervention or, at most, which side in the conflict is supported externally, using a rebel0government dichotomy+ 9 However, many civil wars contain more than one rebel group, and in many cases external states support some, 2+ Regan 2002+ 3+ Heger and Salehyan 2007+ 4+ Cunningham 2010+ 5+ Findley and Teo 2006 discuss the advantages of using an actor-centric approach to studying conflict intervention+ However, they develop a limited rebel0government dichotomy whereas we focus on the particular rebel organizations that receive support+ 6+ See Prunier 2004;andSwami 2004+ 7+ For exceptions, see Bapat 2007;Byman 2005;and Salehyan 2010+ 8+ Gleditsch, Salehyan, and Schultz 2008+ 9+ See Balch-Lindsay, Enterline, and Joyce 2008Gent 2008;Findley and Teo 2006;and Regan 2000+ but not all, rebel organizations+ For instance, in Indonesia, insurgents representing Aceh and East Timor received external support while those fighting for independence for West Papua did not+ In the Colombian conflict, while the Fuerzas Armadas Revolucionarias de Colombia~FARC! received external support from Cuba and other regional actors, the Ejército de Liberación Nacional~ELN!…”
mentioning
confidence: 99%
“…In this article, we seek to advance our knowledge of the relationship between civil and international conflict by examining the factors that influence why certain rebel groups receive external support while others do not+ Empirical analyses of external intervention in civil war often examine what type of conflicts are likely to involve external intervention or, at most, which side in the conflict is supported externally, using a rebel0government dichotomy+ 9 However, many civil wars contain more than one rebel group, and in many cases external states support some, 2+ Regan 2002+ 3+ Heger and Salehyan 2007+ 4+ Cunningham 2010+ 5+ Findley and Teo 2006 discuss the advantages of using an actor-centric approach to studying conflict intervention+ However, they develop a limited rebel0government dichotomy whereas we focus on the particular rebel organizations that receive support+ 6+ See Prunier 2004;andSwami 2004+ 7+ For exceptions, see Bapat 2007;Byman 2005;and Salehyan 2010+ 8+ Gleditsch, Salehyan, and Schultz 2008+ 9+ See Balch-Lindsay, Enterline, and Joyce 2008Gent 2008;Findley and Teo 2006;and Regan 2000+ but not all, rebel organizations+ For instance, in Indonesia, insurgents representing Aceh and East Timor received external support while those fighting for independence for West Papua did not+ In the Colombian conflict, while the Fuerzas Armadas Revolucionarias de Colombia~FARC! received external support from Cuba and other regional actors, the Ejército de Liberación Nacional~ELN!…”
mentioning
confidence: 99%
“…Thus, a greater resource base initially increases the probability of war, and only as income grows to a high level does that tendency eventually decline. A study examining all types of foreign aid interventions from multilateral to unilateral, biased or neutral, found that aid may prolong rather than pacify conflict (Regan 2002). Governments may also utilize food aid to allow inaction in situations of conflict or famine while still potentially maintaining their political base.…”
Section: Emergency Food Aidmentioning
confidence: 99%
“…Previous empirical research has shown that rebel groups typically start out weak relative to the state and launch a rebellion with the expectation that they will be able to mobilise troops. If the government is unable to defeat the rebels in the early stages of conflict, the chances of a swift resolution are remote (Bapat 2005;Regan 2002) and if rebels have a high mobilisation capacity relative to the state's deployment of troops, rebels are more likely to win decisive victories (Cunningham, Gleditsch, and Salehyan 2009). Conflict research has already started using survey data at the individual level to understand rebel group recruitment patterns, participation and attitudes, and how these influence civil war dynamics (Humphreys and Weinstein 2008).…”
Section: Introductionmentioning
confidence: 99%